Toward Economic Diversification in Trinidad and Tobago - Longmore, Rohan; Jaupart, Pascal; Cazorla, Marta Riveira (World Bank, Washington, DC, 2014)
This paper contributes to the predominant diversification debate that has been ongoing in Trinidad and Tobago for more than three decades. The paper makes a determination of the key impediments to the country's attempts at diversification. Econometric techniques are applied on panel data to identify the most significant obstacles to economic diversification for a set of 183 countries. The results indicate that openness to foreign direct investment inflows is the most fundamental driver of diversification. The findings are then applied to the specific case of Trinidad and Tobago through a detailed analysis of the links in the trends followed by foreign direct investment and diversification between 1980 and 2011. Greater openness to foreign direct investment and improving the business climate appear to be key policies the twin-island republic could implement further in order to expand the range of activities of its economic structure.